Analisis Vitamin C dan Protein pada Biji Buah Labu Siam (Sechium edule) - Fadliya, Fadliya; Supriadi, Supriadi; Diah, Anang Wahid M. (Jurnal Akademika Kimia, 2018)
Chayote seeds are found in the middle of the fruit which have flat structures and white. Those seeds has never been used. This study aimed to determine the levels of vitamin C and protein in old chayote fruit seeds. The vitamin C were analyzed using a UV-Vis spectrophotometer, while the protein were analyzed using the Kjeldahl method. Results showed that level of the vitamin C in old fruit seeds was by 0.56%, while the protein level obtained was by 0.81%. This study concluded that old chayote fruit seeds contained protein and vitamin C that can be used as a source of antioxidants and source of beneficial nutrition.